The Impact of Climate Variability on Water Resource Management in Skardu - Sameer, Muhammad; Ali, Zainab; Iqbal, Taimoor; Sibtain, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2025)
Climate variability is posing a great threat to the world particularly in water-scarce regions in every aspect. It is characterized by fluctuating temperatures, shifting precipitation patterns, and extreme weather events.District Skardu, being located in the Karakoram Mountain Range, depends heavily on glacial melt water to meet its water demands in every sector. However, the increasing temperature, rising glacial retreat, unpredictable snowfall, and water shortages in the dry seasons have become great challenges to cope with to the water resource management in region. The current study aims at exploring the impact of climate variability on the water resource management in Skardu, a region heavily reliant on glacial melt water. The study employs a qualitative research approach using secondary data sources. Findings of the study indicate that glacial melting, on one hand, increases water availability temporarily, but on the other hand, poses a great threat by putting long-term sustainability of water at risk. To overcome this challenge, the study suggests some key interventions including,to promote efficient irrigation techniques, to expand water storage infrastructure, and to implement Integrated Water Resource Management, and strengthening climate adaptation policies. Moreover, active community engagement through different seminars, creating awareness among the public regarding efficient use of water, institutional reforms, and scientific monitoring are some other essential measures to take in order to mitigate the risks regarding water shortage and to ensure long-term water security for the region, Skardu and its reliance on downstream regions.